Protein separation from alkaline process water of shrimp waste processing industry using membrane filtration - Thu Nguyen, Le Quynh; Lippich, Heiko; Wagner, Martin; Cornel, Peter; Lutze, Robert; Engelhart, Markus (Vietnam Journal of Chemistry, 2014)
The recovery of protein and caustic soda solution from shrimp waste alkaline process water was experimentally investigated by a two-step filtration process with polymer membranes of different molecular weight cut-offs. Experiments for nine combinations of microfiltration/ultrafiltration and nanofiltration membranes were conducted in batch-mode using a stainless steel stirred cell with a membrane area of 38.5 cm². It could be shown that this process concept is capable of separating protein and dissolved organic carbon from the alkaline hydrolysis of shrimp waste. Totally, more than 30 % of protein was fractionated by the first step filtration while the second step reached a higher protein rejection of more than 88 %. The protein concentrate could be reused as animal feeding and the recovered sodium hydroxide solution couldbe recycled to the production process. Keywords: Membrane filtration, protein recovery, alkaline process water.